Concepções de professores de matemática sobre jogos e sua utilização - Cruz, Alixandre Marques (2023)
This dissertation aims to understand the concepts of Mathematics teachers in the final years of Elementary School in public schools in Poço Redondo (SE) about games and their use. For this, five educational institutions in this municipality that have the final years of Elementary School were selected. Based on this choice, eleven Mathematics teachers who teach in these educational institutions participated in the research. As a theoretical reference, a foundation was sought mainly in Grando (2015, 2004, 1995) to guide the relevance of using games for the teaching-learning process of Mathematics. Regarding the concept of playfulness in the game and its distinction between toy and play, it is based on the notes by Muniz (2021) and Kishimoto (2017). In turn, the understanding of design is guided by Matos and Jardilino (2016). This is a research with a qualitative approach and a case study, in which the data collection instrument used to understand the studied phenomenon of the worker was taken from the application of a semi-structured questionnaire, elaborated from the recommendations of Gil (2008) and Marconi and Lakatos (2003). The analysis of the results was performed using Bardin's (2016) content analysis technique. Through the results, it was possible to identify that all research participants use games in their Mathematics classes. In addition, it was also possible to highlight four categories: the first, the understanding of the game, which the teachers, in their conceptions, reported to be a pedagogical resource that has a methodology, for its development, which involves playfulness, rules, interaction and the ability to develop logical reasoning and, depending on the game, learning certain mathematical contents for those who are playing. The second, stages and challenges of game development, in this one, it is concluded that teachers study, plan and test the game with their families before taking it to be developed in their classes. After this testing, they use it at times that may be related to the before and after the explanation of the content, however, they also highlighted that there are obstacles to its execution. In the third category guided by the types of games, it was found that games such as puzzles and board games are used by most participants, followed by strategy games, card games and those involving content fixation, then digital games and finally gambling and bingo. The fourth and last category, named by the teacher's knowledge about games, concludes that 82% of teachers have knowledge about information about the use of games for teaching Mathematics